Discovering the potential of serious games for transformative sustainability research - Mahsa Motlagh; Andra-Ioana Horcea-Milcu; Bettina König (Discover Sustainability)
Abstract Serious Games (SG) have shown potential as transformative tools in sustainability research. Despite the diverse and widespread adoption of SG as multifunctional tools within collaborative forms of knowledge production, their contribution to transformative research processes is underexplored. Likewise, the selection, alignment, and integration of appropriate SG tailored to specific stages of a transformative research process lacks clear guidelines. To fill this gap, we aim to map the potential of SG in transformative research. We propose to facilitate the assessment of SG alignment and to guide their integration within a transformative research process based on three dimensions: SG complexity levels, SG collaborative engagement levels, and generic stages of transformative research processes. This study explores and organizes the space of potential uses of SG in transformative research based on the three aforementioned dimensions. It provides guidelines to facilitate the assessment of each SG's suitability and its integration within the transformative research process. It operationalizes the proposed conceptual mapping and guidelines with the help of two SG examples. Future work should empirically validate the approach across diverse contexts and address scalability, long-term impacts, and ethical considerations in resource-constrained settings.